Adherence to a Mediterranean-Style Diet and Effects on Cognition in Adults: A Qualitative Evaluation and Systematic Review of Longitudinal and Prospective Trials - Hardman, Roy J.; Kennedy, Greg; Macpherson, Helen; Scholey, Andrew B.; Pipingas, Andrew (Frontiers in Nutrition, 2016)
The Mediterranean-style diet (MedDiet) involves substantial intake of fruits, vegetables, and fish, and a lower consumption of dairy, red meat, and sugars. Over the past 15 years much empirical evidence supports the suggestion that a MedDiet may be beneficial with respect to reducing the incidence of cardiovascular disease, cancer, metabolic syndrome, and dementia. A number of cross-sectional studies that have examined the impact of MedDiet on cognition have yielded largely positive results. The objective of this review is to evaluate longitudinal and prospective trials to gain an understanding of how a MedDiet may impact cognitive processes over time. The included studies were aimed at improving cognition or minimizing of cognitive decline. Studies reviewed included assessments of dietary status using either a food frequency questionnaire or a food diary assessment. Eighteen articles meeting our inclusion criteria were subjected to systematic review. These revealed that higher adherence to a MedDiet is associated with slower rates of cognitive decline, reduced conversion to Alzheimer’s disease (AD) and improvements in cognitive function. The specific cognitive domains that were found to benefit with improved Mediterranean Diet Score (MedDietS) were memory (delayed recognition, long-term and working memory) executive function, and visual constructs. The current review has also considered a number of methodological issues in making recommendations for future research. The utilisation of a dietary pattern such as the Mediterranean style diet will be essential as part of the armamentarium to maintain quality of life and reduce the potential social and economic burden of dementia. Key Words: Nutrition, cognition, Mediterranean diet, clinical trials